RE-DESIGN LOGO USAHA KECIL MENENGAH PADA TOKO GIBRAN COLLECTION DI PULANG UNTUNG JAWA - Fauzi, Muhammad (Universitas Esa Unggul, 2018)
AbstractWith the increase in tourists to the island of Untung Jawa which is getting sharper so that the Small and Medium Business Actors